2019
DOI: 10.1103/physrevc.100.054905
|View full text |Cite
|
Sign up to set email alerts
|

pT -dependent particle number fluctuations from principal-component analyses in hydrodynamic simulations of heavy-ion collisions

Abstract: We carry out a principal component analysis of fluctuations in a hydrodynamic simulation of heavy-ion collisions, and compare with experimental data from the CMS collaboration. The leading and subleading principal components of elliptic and triangular flow reproduce the trends seen in data. By contrast, the principal components of multiplicity fluctuations show an interesting difference in their pT dependence for simulations compared to experimental data. Specifically, the leading component increases with pT i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…A recent study [261] showed that the subleading principal components of anisotropic flow can reveal details of the hydrodynamic response to small-scale structures in the initial density profiles. Similar studies have also been performed to understand the event-by-event fluctuations in particle multiplicity and radial flow [260,262]. The PCA recently has been applied in unsupervised learning to test whether a machine can directly discover anisotropic flow coefficients from the high-volume simulation data without explicit instructions from human-beings [263].…”
Section: Applications Of Statistics and Machine-learning Techniquesmentioning
confidence: 99%
“…A recent study [261] showed that the subleading principal components of anisotropic flow can reveal details of the hydrodynamic response to small-scale structures in the initial density profiles. Similar studies have also been performed to understand the event-by-event fluctuations in particle multiplicity and radial flow [260,262]. The PCA recently has been applied in unsupervised learning to test whether a machine can directly discover anisotropic flow coefficients from the high-volume simulation data without explicit instructions from human-beings [263].…”
Section: Applications Of Statistics and Machine-learning Techniquesmentioning
confidence: 99%
“…For the simple cases considered here, principal component analysis (PCA) is quite effective (see Refs. [59][60][61][62][63] for other applications of PCA to problems in ultrarelativistic heavy-ion collisions). Intuitively, PCA quantifies the variations of a data set in different directions and associates an explained variance with each of them.…”
mentioning
confidence: 99%
“…In contrast, the first approach assigns equal weight in all p T bins. A recent work [23,24] argues that PCA modes extracted from normalized scheme (w(p T ) = 1) seem more accurately reflect the underlying flow modes.…”
Section: Test Setupmentioning
confidence: 99%